FRI0363 CLINICAL PREDICTORS OF SECUKINUMAB RETENTION IN A REAL WORLD COHORT OF PATIENTS WITH PSORIATIC ARTHRITIS AND AXIAL SPONDYLOARTHRITIS. (2nd June 2020) - Tindell, A.; Mcgucken, A.; Batool, S.; Siebert, S.
Abstract : Background: There are increasing treatment options for patients with psoriatic arthritis (PsA) and axial spondyloarthritis (AxSpA). Whilst there are several studies identifying predictors of response to TNF inhibitors 1 there is little data so far predicting response to the IL-17A inhibitor secukinumab which given its different mechanism of action may have different predictors of response. Objectives: To identify demographic or clinical factors at initiation of secukinumab associated with stopping treatment due to inefficacy in PsA and in AxSpA in a real world cohort. Methods: Retrospective analysis of all rheumatology patients' notes in Glasgow who had received secukinumab. Demographics, disease activity at baseline and retention of secukinumab were collected from medical records in patients with a diagnosis of PsA or AxSpA. Patients who discontinued due to adverse events or other events (e.g. pregnancy) were excluded. Patients who remain on secukinumab but have not yet had their six-month review to assess response or who started secukinumab via a clinical trial were also excluded. Unpaired T-test of unequal variance used to assess differences between groups with p-value ≤0.05 considered significant. Results: 352 rheumatology patients in Glasgow had ever received secukinumab. 266 had PsA, 76 had AxSpA (others: SAPHO, JIA, reactive arthritis). 77 PsA patients discontinued secukinumab, 48 due to inefficacy. 157 PsA patients remain on secukinumab and have had at least an initial six-month review. Table 1 shows results for PsA. Inefficacy was associated with higher levels of current smoking and higher levels of ESR and CRP but not tender or swollen joints. 21 AxSpA patients discontinued secukinumab, 13 due to inefficacy. 49 AxSpA patients remain on secukinumab and have had at least an initial six-month review. AxSpA patients who stopped due to inefficacy had higher mean BASDAI (8.47 vs 7.02, p=0.007) but there was no difference in mean ESR (31 vs 27.1, p=0.31) or CRP (23.6 vs 23.0, p=0.48). Surprisingly, disease duration was lower in inefficacy group (7.8 years vs 13.5, p= 0.003); this could reflect a higher proportion in the inefficacy group with non-radiographic AxSpA which is known to be associated with earlier disease and to have a lower response to biologic treatments than ankylosing spondylitis. Smoking did not show significant difference in AxSpA but numbers are small and there is numerically higher level of smoking in the inefficacy group (58% vs 32%, p=0.063). No other significant differences in demographics or clinical characteristics were noted. Conclusion: Smoking predicted inefficacy in secukinumab in PsA patients, with a similar trend in AxSpA patients, reinforcing the importance of promoting smoking cessation. Higher levels of ESR and CRP negatively predicted secukinumab response in PsA. High BASDAI and low disease duration in AxSpA predicted inefficacy. These clinical factors may be helpful in informing treatment decisions in PsA and AxSpA in the absence of therapeutic biomarkers. References: [1]Maneiro JR et al. Predictors of response to TNF antagonists in patients with ankylosing spondylitis and psoriatic arthritis: systematic review and meta-analysis. RMD Open . 2015;1(1):e000017. Disclosure of Interests: Alistair Tindell: None declared, Andrew McGucken: None declared, Saira Batool: None declared, Stefan Siebert Grant/research support from: BMS, Boehringer Ingelheim, Celgene, GlaxoSmithKline, Janssen, Novartis, Pfizer, UCB, Consultant of: AbbVie, Boehringer Ingelheim, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Celgene, Janssen, Novartis